ETNOBOTANI TANAMAN OBAT OLEH MASYARAKAT DUSUN 2 DESA SEI SIUR PANGKALAN SUSU - Izzatul Umma; Adi Bejo Suwardi (Universitas PGRI Banyuwangi, Jalan Ikan Tongkol No 01, Telp (0333) 421593, 428592 Banyuwangi 68416, 2026)
This study aims to investigate the use of traditional medicinal plants by the community of Dusun 2, Sei Siur Village, Pangkalan Susu Subdistrict, Langkat Regency, North Sumatra. The study employed a descriptive-exploratory method using a survey approach. Data were collected through observation, structured and semi-structured interviews, and documentation from 20 respondents aged 21–55 years. Data were analyzed using qualitative and quantitative descriptive methods, employing ethnobotanical indices such as Relative Frequency of Citation (RFC), Use Value (UV), and Cultural Importance Index (CI). The results indicate that the community utilizes 10 types of medicinal plants belonging to 7 plant families, with the Zingiberaceae family being the most dominant. The most commonly used plant parts are leaves and rhizomes. The most common method of preparation is boiling, while the most common method of use is ingestion. The bidara plant (Ziziphus mauritiana) has the highest UV value of 0.85, while the kitolod plant (Isotoma longiflora) has the highest CI value of 0.6. The research results indicate that the community of Dusun 2, Sei Siur Village, still preserves traditional knowledge regarding the use of medicinal plants as part of local wisdom passed down from generation to generation.